2021
DOI: 10.12688/wellcomeopenres.16432.1
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of ethics and regulatory authorities on human infection studies: Proceedings of an engagement workshop in Zambia

Abstract: Human infection studies (HIS) have generally been used as a tool in the pathway for vaccine development in high income settings. Over the last decade, this model has been implemented in LMICs with the aim of accelerating development of next generation vaccines that would perform better in these settings. However, in most LMICs, the ethics and regulatory framework for the conduct of these studies are not in place. In Zambia, these studies are yet to be conducted and thus we conducted a stakeholder engagement wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This process of engagement was recommended by Ugandan stakeholders in preparation for CHI-S (Elliott et al, 2018 ). Similarly, other CHI studies have also recommended and conducted community engagements with the target communities in disease-endemic countries such as Zambia (Kunda-Ng’andu et al, 2021 ), Vietnam (Kestelyn et al, 2019 ), India (Vaz et al, 2019 , 2020 ), Malawi (Kapumba et al, 2020 ), Kenya (Njue et al, 2018 ), and Gabon (Alabi et al, 2021 ). The studies showed that participants are able to understand the processes involved during a CHI.…”
Section: Discussionmentioning
confidence: 99%
“…This process of engagement was recommended by Ugandan stakeholders in preparation for CHI-S (Elliott et al, 2018 ). Similarly, other CHI studies have also recommended and conducted community engagements with the target communities in disease-endemic countries such as Zambia (Kunda-Ng’andu et al, 2021 ), Vietnam (Kestelyn et al, 2019 ), India (Vaz et al, 2019 , 2020 ), Malawi (Kapumba et al, 2020 ), Kenya (Njue et al, 2018 ), and Gabon (Alabi et al, 2021 ). The studies showed that participants are able to understand the processes involved during a CHI.…”
Section: Discussionmentioning
confidence: 99%